PENGARUH KETERSEDIAAN AIR TERHADAP HASIL DAN KANDUNGAN KURKUMIN KUNYIT (Curcuma domestica Valeton) - Cholilah Suciastuti (LPPM Universitas Negeri Jakarta, 2019)
Turmeric is a herb and medicinal plant that has many functions like being often used as spices, preservatives, dyes, cosmetics, and paint raw materials, and also turmeric plants are widely used as medicinal plants, because of the active ingredient (secondary metabolites) found in turmeric which is curcumin. Curcumin has function in providing natural color in turmeric, besides that it plays a role in the health sector as antihepatotoxic, antiedemic, antioxidant, anti inflammatory, anticancer and so on. Water availability play important role in growth and development of a plant. Internally, lack of water can make plant in drought condition, the physiology process of the plant disturbed, producing secondary metabolith and excess water can make the growth of the plant obstructed.This study aims to determine the effect of water availability from the beginning to harvesting turmeric plants on the yield of turmeric (Curcuma domestica Val.) and to determine the effect of water availability before harvesting turmeric plants on the level curcumin of turmeric plants (Curcuma domestica Val.). Keywords: curcumin, turmeric, water availability, yield